The Application of Digital Literacy Based on Local Wisdom in Indonesian Language Learning in Elementary Schools - Rohmat Suryanto; Farida Nugrahani; Nurmaningsih Nurmaningsih (Teknodika, 2026)
This research aims to describe the implementation of digital literacy integrated with local wisdom in Indonesian language learning at elementary schools. The study employs a descriptive qualitative method. The data consists of information related to the application of local wisdom-based digital literacy in Indonesian language learning at the elementary level. Data sources include school principals, teachers, students, the learning process, and supporting documents. Sampling was conducted using purposive sampling techniques. Data collection methods involved observation, in-depth interviews, and document analysis. Data validation was ensured through source and method triangulation. Data analysis was performed interactively through several stages: data collection, data condensation, data visualization, and conclusion drawing/verification. The results indicate that teachers systematically designed lessons utilizing digital media containing local wisdom content, such as folktales, oral traditions, and local cultural values. The learning process strengthened students' understanding of local cultural values. Through collaborative methods and authentic assessments, students actively engaged in analyzing, creating, and presenting digital works based on local wisdom. This strategy supported learning objectives while promoting cultural preservation and the development of 21st-century skills such as critical thinking, creativity, and collaboration. The implementation results demonstrate that combining digital competencies with local values can enhance literacy skills and foster cultural identity awareness from an early age.